Potentiometric Carbon Monoxide Sensors Using an Anion-Conducting Polymer Electrolyte and Au-Loaded SnO2 Electrodes. Issue 7 (14th April 2016) - Hyodo, Takeo; Goto, Toshiyuki; Ueda, Taro; Kaneyasu, Kazunari; Shimizu, Yasuhiro
Abstract : Potentiometric gas sensors using an anion-conducting polymer as an electrolyte and SnO2 loaded with or without 2.0 wt% Au as an electrode material were fabricated and the CO-sensing properties were investigated mainly in wet synthetic air (57%RH) at 30°C. Loading of Au onto SnO2 powders by precipitation-deposition technique was quite effective in improving the sensing properties to CO and H2, and the magnitude of CO response was larger than that of H2 response. In addition, the CO response was largely dependent on concentration of O2 in the gaseous atmosphere. These results indicate that electromotive force of the sensor is probably determined by mixed potential resulting from CO oxidation and O2 reduction. Heat treatment of the Au-loaded SnO2 powder under reducing atmosphere decreased the H2 -sensing properties, and thus largely enhanced the CO selectivity against H2 . Especially, the sensor using Au-loaded SnO2 which was heat-treated in H2 at 250°C showed large CO response, the largest CO selectivity against H2, and the fastest response and recovery speeds among all the sensors tested, while storage of the sensor under normal atmosphere weakened the effect of the heat-treatment in H2 at 250°C on the CO-sensing properties.